Phenolic resin-based composite bipolar plate and preparation method thereof
By using low-cost inorganic whiskers and organic fibers to replace carbon fibers and carbon tubes, and perform surface modification, combined with phenolic resin modification, uniformly dispersing graphite materials, the problem of high cost of phenolic resin-based composite bipolar plates is solved, and the problem of high cost of phenolic resin-based composite bipolar plates is achieved. High thermal conductivity, high strength and low cost performance of fuel cell bipolar plates.
Patent Information
- Application Number
- CN202411417591.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-27
AI Technical Summary
While maintaining mechanical properties and conductivity, the existing phenolic resin-based composite bipolar plates have high manufacturing costs, and the addition of carbon fibers and carbon nanotubes affects the cost. How to reduce costs without damaging performance is a challenge.
Use low-cost inorganic whiskers and organic fibers to replace carbon fibers and carbon tubes. By modifying the surface of fibers and whiskers, combining the modification of phenolic resin, uniformly disperse the graphite material, reduce hydrogen permeability and retain conductivity, and utilize conductivity Carbon black and chopped carbon fibers build conductive networks to improve bending strength and thermal conductivity.
A low-cost high-thermal conductivity and high-strength fuel cell bipolar plate has been achieved, with a conductivity of 190S/cm, a thermal conductivity of 25W/m·k, and a bending strength of about 65Mpa, which significantly reduces the preparation cost of composite bipolar plates.
Smart Images

Figure BDA0005079864640000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of bipolar plates for fuel cells, and in particular to a phenolic resin-based composite bipolar plate and a preparation method thereof. Background Art
[0002] Due to its high energy conversion efficiency and zero emission characteristics, fuel cells are becoming a clean energy technology that is being focused on worldwide research and development. As one of the core components of fuel cells, bipolar plates not only account for a significant share of the cost structure, but also play a decisive role in performance including current density, airtightness and service life. Compared with traditional graphite and metal bipolar plates, composite bipolar plates are favored for their easy processing, high cost-effectiveness and corrosion resistance. In order to promote the development of fuel cell technology, it is necessary to solve the cost problem of composite bipolar plates, improve their performance, overcome various problems in practical applications, and ensure reliability and efficiency in various practical application scenarios.
[0003] Chinese patent CN100479239C discloses a carbon nanotube-enhanced phenolic resin-based fuel cell bipolar plate, wherein the graphite content is 72-88%, the phenolic resin content is 11.5-23%, and the carbon nanotube content is 0.5-5%. Its volume conductivity is 100-200S / cm and the bending strength is 55-75MPa. High content of graphite powder will increase the cost of composite bipolar plates. Chinese patent CN118248883 A discloses a multi-step rapid molding technology for fuel cell bipolar plates, wherein the graphite powder content is only 10-30%, and the content of thermosetting resin is 70-90%. The obtained bipolar plate has a conductivity of 108S / cm and a bending strength of ≥50MPa. Carbon fiber, conductive carbon, and carbon nanotubes can significantly improve the conductivity and bending strength of bipolar plates. Chen Hui and others from Hunan University systematically studied the effects of carbon fiber and conductive carbon content on the mechanical properties of fuel cell bipolar plates, but their conductivity was less than 100S / cm and their flexural strength was less than 40MPa (Journal of Composite Materials, 2015, 32, 744). Song Jianbin and others used phenolic resin-based bipolar plate materials modified with biomass lignin, and achieved a conductivity of 500S / cm and a flexural strength of 68MPa at 40% modified phenolic resin, 30% carbon fiber and 30% graphite addition (Plastics Industry 2018, 46, 147).
[0004] Carbon fiber and carbon nanotubes can significantly improve the electrical conductivity and mechanical strength of composite bipolar plates, but their addition amount is also an important factor affecting the cost of composite bipolar plates. Reducing the amount of these conductive and toughening fillers can significantly reduce their manufacturing costs; however, the lack of toughening materials such as carbon fiber and carbon nanotubes will lead to a significant decrease in the mechanical properties of composite bipolar plates. How to maintain the mechanical properties and electrical conductivity of composite bipolar plates while reducing the cost of bipolar plate manufacturing is an inevitable problem faced in the industrialization process of phenolic resin-based composite bipolar plates.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a phenolic resin-based composite bipolar plate and a preparation method thereof, so as to solve the above-mentioned problems and achieve the goal of maintaining the mechanical properties and electrical conductivity of the composite bipolar plate while reducing its manufacturing cost.
[0007] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:
[0008] The present application provides a method for preparing a phenolic resin-based composite bipolar plate, comprising the following steps:
[0009] S1: uniformly mixing raw materials including phenolic resin, graphite material, chopped carbon fiber, carbon nanotube, fiber additive and conductive carbon black and drying them at 35-60° C. to obtain a mixture;
[0010] The phenolic resin may be solid or powder, and may be dissolved in ethanol; preferably, the phenolic resin is modified by a modifier before the mixing;
[0011] The modifier includes one or more of lignin, tannin, furfural, and furfuryl alcohol; preferably, the amount of the modifier accounts for 0.5-10wt.% of the mass of the phenolic resin;
[0012] The length of the chopped carbon fiber is 3 mm or less;
[0013] The graphite material includes graphite powder and / or expanded graphite; preferably, the mass ratio of the graphite powder to the expanded graphite is 1:0.1-0.5.
[0014] Optionally, the composition of the raw materials includes, by weight: 12-38 parts of phenolic resin, 12-38 parts of graphite powder, 0.2-5 parts of expanded graphite, 0.1-2 parts of chopped carbon fiber, 0-1 parts of carbon nanotubes, 5-30 parts of fiber additives, 2-16 parts of conductive carbon black; the sum of all the raw materials is 100 parts. Since the present invention uses a relatively low content of phenolic resin, the gas in the mixture is squeezed out, and the powders are further mixed and tightly combined, and the raw materials are mixed evenly using a high mixer and a kneading machine, the purpose of finally increasing the density of the plate and reducing the porosity of the plate is achieved.
[0015] Further, the fiber additive includes modified calcium sulfate whiskers, modified calcium carbonate whiskers, modified potassium titanate whiskers, modified aluminum borate whiskers, modified magnesium oxide whiskers, modified aluminum oxide whiskers, modified glass fibers, modified basalt fibers, aramid fibers, and polyimide fibers;
[0016] The modification includes: surface modification using a silane coupling agent;
[0017] The silane coupling agent is selected from KH550, KH560 and KH520.
[0018] S2: Extruding the mixture obtained in S1 through a twin-screw extruder and injecting it into a mold, subjecting it to a pressurization treatment, decompressing it and demolding it, and finally subjecting it to a heat treatment to obtain the phenolic resin-based composite bipolar plate;
[0019] The extrusion temperature is 60-100°C;
[0020] The pressure treatment comprises: pre-pressing at 6-10 MPa for 1-5 min, then increasing the pressure to 50-90 MPa, maintaining the pressure at 140-230° C. for 5-30 min;
[0021] The heat treatment temperature is 80-120° C. and the time is 0.5-12 hours.
[0022] Further preferably, the mixing in step S1 further comprises: firstly mixing the phenolic resin, the chopped carbon fibers and the fiber additives, and stirring at 40-50° C. for 0.5-1 h; then heating to 70-90° C., adding other raw materials and continuing stirring and mixing for 0.5-2 h.
[0023] The invention provides a phenolic resin-based composite bipolar plate, which is prepared by the preparation method.
[0024] First, in response to the high cost of manufacturing composite bipolar plates in the prior art, the present application creatively uses low-cost inorganic whiskers, fibers and organic fibers as fiber additives to partially replace the toughening effect of carbon fibers and carbon tubes in bipolar plates. Due to the large differences in density of these inorganic and organic whiskers, fibers and graphite, and the significant differences in surface functional groups and surface wettability, different types of fillers agglomerate in the phenolic resin matrix and are difficult to disperse evenly, which significantly affects its mechanical properties as well as electrical and thermal conductivity.
[0025] Based on this, the present application creatively solves the problem of filler separation and agglomeration caused by large differences in density, surface groups, surface wettability, and interaction with the matrix resin by modifying the surface of fibers and whiskers in combination with the modification of phenolic resin. It is evenly dispersed with graphite in the composite material, and on the basis of improving its bending strength, the hydrogen permeability is reduced, the conductivity and heat transfer performance of the composite bipolar plate are retained, and the manufacturing cost of the composite bipolar plate is reduced.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The main raw materials used in this application, graphite and phenolic resin, are bulk chemicals. Calcium sulfate whiskers, aluminum borate and other whisker materials, basalt fibers, glass fibers and other fibers are also low-cost chemical raw materials. In addition, the amount of expanded graphite and carbon fiber is less than 5 parts, and the content of carbon nanotubes is less than 1 part. Conductive carbon black and a small amount of chopped carbon fibers are used to construct a conductive network with graphite-based materials. Inorganic whiskers and organic fibers are used to toughen and enhance and ensure the mechanical properties of the bipolar plate, thereby significantly reducing the preparation cost of the composite bipolar plate.
[0028] The bipolar plate prepared by the method of the present application is a low-cost fiber / whisker reinforced high thermal conductivity and high strength fuel cell bipolar plate, whose electrical conductivity can reach 190S / cm, thermal conductivity can reach 25W / m·k, and bending strength can be maintained at about 65Mpa. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] The composite bipolar plate is prepared according to the method provided by the present invention, and the specific steps are as follows:
[0032] Weigh 38 parts of phenolic resin modified with 0.5wt.% tannin modifier, 15 parts of graphite powder, 2 parts of expanded graphite, 2 parts of 2mm chopped carbon fibers, 1 part of carbon nanotubes, 30 parts of 3mm chopped basalt fibers modified with KH550, and 12 parts of conductive carbon black, mix them evenly, and extrude the mixture through a twin-screw extruder, the outlet temperature of the twin-screw extruder being 60°C;
[0033] The extrudate was injected into the mold, pre-pressed at 6 MPa for 5 min, then pressurized to 70 MPa, maintained at 200°C for 50 min, then decompressed and demoulded, and heat treated at 80°C for 0.5 h to obtain a composite bipolar plate.
[0034] Example 2
[0035] The composite bipolar plate is prepared according to the method provided by the present invention, and the specific steps are as follows:
[0036] Weigh 38 parts of phenolic resin modified with 10 wt.% lignin modifier, 38 parts of graphite powder, 4.8 parts of expanded graphite, 0.2 parts of chopped carbon fiber with a length of 2 mm, 5 parts of aluminum borate whiskers modified with KH520, and 14 parts of conductive carbon black, mix them evenly, and extrude the mixture through a twin-screw extruder, and the outlet temperature of the twin-screw extruder is 100° C.
[0037] The extrudate was injected into the mold, pre-pressed at 10 MPa for 5 min, then pressurized to 50 MPa, maintained at 220°C for 30 min, then decompressed and demoulded, and heat treated at 80°C for 12 h to obtain a composite bipolar plate.
[0038] Example 3
[0039] The composite bipolar plate is prepared according to the method provided by the present invention, and the specific steps are as follows:
[0040] Weigh 18 parts of phenolic resin modified with 5% furfural, 36 parts of graphite powder, 5 parts of expanded graphite, 1 part of chopped asphalt-based carbon fiber, 24 parts of aramid fiber, and 16 parts of conductive carbon black, mix them evenly, and extrude the mixture through a twin-screw extruder, the outlet temperature of the twin-screw extruder is 80°C;
[0041] The extrudate was injected into the mold, pre-pressed at 10 MPa for 5 min, then pressurized to 90 MPa, maintained at 160°C for 30 min, then decompressed and demoulded, and heat treated at 80°C for 12 h to obtain a composite bipolar plate.
[0042] Example 4
[0043] The composite bipolar plate is prepared according to the method provided by the present invention, and the specific steps are as follows:
[0044] Weigh 29 parts of phenolic resin modified with 0.5% furfuryl alcohol, 29 parts of graphite powder, 5 parts of expanded graphite, 2 parts of chopped carbon fiber, 15 parts of KH560 modified potassium titanate whisker, and 20 parts of conductive carbon black, mix them evenly, and extrude the mixture through a twin-screw extruder at an extruder outlet temperature of 100°C;
[0045] The extrudate was injected into the mold, pre-pressed at 8 MPa for 5 min, then pressurized to 90 MPa, maintained at 180°C for 30 min, then decompressed and demoulded, and heat treated at 120°C for 12 h to obtain a composite bipolar plate.
[0046] Example 5
[0047] The composite bipolar plate is prepared according to the method provided by the present invention, and the specific steps are as follows:
[0048] Weigh 38 parts of phenolic resin modified with 10% lignin modifier, 38 parts of graphite powder, 4.8 parts of expanded graphite, 0.2 parts of chopped carbon fiber with a length of 2 mm, 5 parts of aluminum borate whiskers modified with KH520, and 14 parts of conductive carbon black for later use;
[0049] First, 38 parts of phenolic resin modified with 10% lignin modifier, 0.2 parts of chopped carbon fiber with a length of 2 mm and 5 parts of aluminum borate whiskers modified with KH520 were mixed for the first time and stirred at 40°C for 0.5h; then the temperature was raised to 80°C, and other raw materials were added and stirred and mixed for 1h. After mixing evenly, the mixture was extruded through a twin-screw extruder at an extruder temperature of 100°C;
[0050] The extrudate was injected into the mold, pre-pressed at 10 MPa for 5 min, then pressurized to 50 MPa, maintained at 220°C for 30 min, then decompressed and demoulded, and heat treated at 80°C for 12 h to obtain a composite bipolar plate.
[0051] Comparative Example 1
[0052] The only difference from Example 1 is that the phenolic resin used is a conventional phenolic resin without modification.
[0053] Comparative Example 2
[0054] The difference from Example 2 is that the raw material aluminum borate whisker used is not modified.
[0055] The performance of the composite bipolar plates prepared in the examples and comparative examples of the present application was tested, and the specific results are shown in Table 1 below:
[0056] Table 1 Performance test results of composite bipolar plates prepared in Examples and Comparative Examples
[0057]
[0058] It can be seen from Table 1 that the composite bipolar plates prepared by the method provided in the present application generally have higher bending strength, electrical conductivity and thermal conductivity. By comparing Example 5 with Example 2, it can be seen that adjusting the mixing step, first mixing the modified phenolic resin with chopped carbon fibers and modified aluminum borate whiskers, and then mixing with graphite materials and other raw materials, can significantly improve the bending strength of the bipolar plate. This is because the addition of high-component solid-phase fillers will cause a sharp increase in the viscosity of the system. Under high viscosity conditions, the uniform dispersion of carbon fibers and aluminum borate whiskers requires high shear mixing conditions, which can easily lead to the breakage of the fiber material and the decrease in secondary mechanical properties. Therefore, the present invention only adds fiber material during the first mixing, so that it can be evenly dispersed when the system viscosity is relatively low, maintaining its integrity, and utilizing the characteristics of the second mixing that the higher temperature is conducive to the decrease in the viscosity of the system, and further introducing graphite and expanded graphite to make it evenly dispersed.
[0059] By comparing Example 1 with Comparative Example 1, it can be seen that, under the same other conditions, Comparative Example 1 using conventional phenolic resin cannot achieve the effect of the present application; at the same time, by Example 2 and Comparative Example 2, it can be seen that only modifying the phenolic resin without modifying the fiber additive (whiskers or fibers) also cannot achieve the purpose of the present application. This is because if the fiber additive is not modified to change its surface chemical environment, the whiskers or fibers such as aluminum borate are easily agglomerated in the phenolic resin matrix due to the bonding effect of hydrogen bonds, making it difficult to evenly disperse and difficult to play the reinforcing role of the fiber, resulting in a significant decrease in its mechanical and other properties.
[0060] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A method for preparing a phenolic resin-based composite bipolar plate, characterized in that: The following steps are involved: S1: uniformly mixing raw materials including phenolic resin, graphite material, chopped carbon fiber, carbon nanotubes, fiber additives and conductive carbon black, and drying them by air blast at 35-60° C. to obtain a mixture; S2: Extruding the mixture obtained in S1 through a twin-screw extruder and injecting it into a mold, subjecting it to a pressurization treatment, decompressing it and demolding it, and finally subjecting it to a heat treatment to obtain the phenolic resin-based composite bipolar plate; The length of the chopped carbon fiber is 3 mm or less.
2. The preparation method according to claim 1, characterized in that: The phenolic resin is modified by a modifier before the mixing.
3. The preparation method according to claim 2, characterized in that: The modifier includes one or more of lignin, tannin, furfural and furfuryl alcohol.
4. The preparation method according to claim 2 or 3, characterized in that: The amount of the modifier used accounts for 0.5-10% of the mass of the phenolic resin.
5. The preparation method according to claim 1, characterized in that: The graphite material includes graphite powder and / or expanded graphite; Preferably, the mass ratio of the graphite powder to the expanded graphite is 1:0.1-0.
5.
6. The preparation method according to claim 5, characterized in that: The raw materials include, by weight: 12-38 parts of phenolic resin, 12-38 parts of graphite powder, 0.2-5 parts of expanded graphite, 0.1-2 parts of chopped carbon fiber, 0-1 parts of carbon nanotubes, 5-30 parts of fiber additives, and 2-16 parts of conductive carbon black; The total number of parts of all ingredients is 100 parts.
7. The preparation method according to claim 1, characterized in that: The fiber additives include modified calcium sulfate whiskers, modified calcium carbonate whiskers, modified potassium titanate whiskers, modified aluminum borate whiskers, modified magnesium oxide whiskers, modified aluminum oxide whiskers, modified glass fibers, modified basalt fibers, aramid fibers, and polyimide fibers; The modification includes: surface modification using a silane coupling agent; The silane coupling agent is selected from KH550, KH560 and KH520.
8. The preparation method according to claim 1, characterized in that: The step S2 also satisfies one or more of the following conditions: a. The extruder outlet temperature is 60-100°C; b. The pressure treatment comprises: pre-pressing at 6-10 MPa for 1-5 min, then increasing the pressure to 50-90 MPa, maintaining the pressure at 140-230 ° C for 5-30 min; c. The heat treatment temperature is 80-120°C and the time is 0.5-12h.
9. The preparation method according to claim 1, characterized in that: The mixing in step S1 also includes: firstly mixing the phenolic resin, the chopped carbon fibers and the fiber modifier, stirring at 40-50° C. for 0.5-1 h; then heating to 70-90° C., adding other raw materials and continuing stirring and mixing for 0.5-2 h.
10. A phenolic resin-based composite bipolar plate, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.